2022
DOI: 10.3390/cimb44030089
|View full text |Cite
|
Sign up to set email alerts
|

hERG1 Potassium Channel Expression in Colorectal Adenomas: Comparison with Other Preneoplastic Lesions of the Gastrointestinal Tract

Abstract: Preneoplastic lesions represent a useful target for early diagnosis and follow-up of gastrointestinal malignancies. hERG1 channel expression was tested by immunohistochemistry (IHC) in a cohort of colorectal adenoma samples belonging to Italian subjects. Overall, hERG1 was expressed in 56.5% of cases with both high staining intensity and a high percentage of positive cells. Moreover, hERG1 was expressed in a higher percentage of dysplastic adenomas with respect to hyperplastic lesions, and the proportion of po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…High expression of genes encoding Kv11.1 channels is associated with favorable prognosis in estrogen receptor-negative breast cancer ( 75 ). Extensive expression of Kv11.1 channels in gastrointestinal tumors may serve as an early diagnostic marker ( 76 ). Expression of KCNN4 is associated with disease-free survival, immune infiltration, and several other clinicopathological features and can serve as a diagnostic and prognostic biomarker in TC ( 86 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High expression of genes encoding Kv11.1 channels is associated with favorable prognosis in estrogen receptor-negative breast cancer ( 75 ). Extensive expression of Kv11.1 channels in gastrointestinal tumors may serve as an early diagnostic marker ( 76 ). Expression of KCNN4 is associated with disease-free survival, immune infiltration, and several other clinicopathological features and can serve as a diagnostic and prognostic biomarker in TC ( 86 ).…”
Section: Discussionmentioning
confidence: 99%
“…High Kv11.1 expression is associated with a favorable prognosis in estrogen receptor-negative breast cancer, and NS1643, a Kv11.1 activator, reduces the metastatic spread of breast tumors in vivo by inhibiting cell motility via β-catenin ( 75 ). Researchers have found that Kv11.1 is highly expressed in precancerous lesions of the gastrointestinal tract, and Kv11.1 can be used as an early diagnostic marker for gastrointestinal tumors ( 76 ). In addition, Kv11.1 is widely expressed in metastatic CRC, and combined treatment with Kv11.1 blockers and bevacizumab inhibits local tumor growth and metastatic spread ( 77 ).…”
Section: Role Of Potassium Channel In Diagnosis and Treatment Of Tumormentioning
confidence: 99%
“…In the colon–rectum, hERG1 is not expressed in healthy colonic mucosa and sigma diverticulitis (Dolderer et al., 2010; Lastraioli et al., 2004). Precancerous colon rectal adenoma lesions express the channel, although expression levels increase in high‐grade dysplastic colon rectal adenomas (Lastraioli et al., 2022). On the other hand, both the KCNH2 transcript and the hERG1 protein are highly expressed in CRC cell lines and primary samples (Lastraioli et al., 2004).…”
Section: Introductionmentioning
confidence: 99%